2015
DOI: 10.1097/dcr.0000000000000409
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Physiologic Sexual Dysfunction Is High Following Treatment for Rectal Cancer

Abstract: The results of this study show that sexual problems continue to increase up to 1 year after surgery. Despite this, sexual interest in both male and female patients remained relatively unchanged suggesting that other aspects of sexuality, not just physiologic function, also need to be evaluated. Future studies to assist and educate physicians on how to initiate a discussion about sexuality and identify patients in "distress" because of sexual problems are important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 11 publications
0
9
0
2
Order By: Relevance
“…70 Vanliga symtom som negativt påverkar hälsorelaterad livskvalitet hos personer med bröst-och kolorektalcancer som genomgått kirurgi och cytostatikabehandling inkluderar fysiska, psykiska och sociala begränsningar. Fysiskt nedsatt funktion har rapporterats på grund av smärta i kroppen, 71 fatigue och sömnproblem, 72 missnöje med sin kropp och nedsatt sexuell lust 73,74 men också psykisk påverkan på grund av oro, depression 75 och kognitionsproblem. 76,77 Personer med kolorektalcancer rapporterar även att stomi till följd av kirurgi är ett fysiskt och socialt problem som inverkar på den hälsorelaterade livskvaliteten.…”
Section: Hälsorelaterad Livskvalitet Vid Cancer Och Cancerbehandlingunclassified
“…70 Vanliga symtom som negativt påverkar hälsorelaterad livskvalitet hos personer med bröst-och kolorektalcancer som genomgått kirurgi och cytostatikabehandling inkluderar fysiska, psykiska och sociala begränsningar. Fysiskt nedsatt funktion har rapporterats på grund av smärta i kroppen, 71 fatigue och sömnproblem, 72 missnöje med sin kropp och nedsatt sexuell lust 73,74 men också psykisk påverkan på grund av oro, depression 75 och kognitionsproblem. 76,77 Personer med kolorektalcancer rapporterar även att stomi till följd av kirurgi är ett fysiskt och socialt problem som inverkar på den hälsorelaterade livskvaliteten.…”
Section: Hälsorelaterad Livskvalitet Vid Cancer Och Cancerbehandlingunclassified
“…Patients feel that sexual function is relevant and needs to be discussed [2][3] and they also consider a physician's responsibility to initiate discussions about sexual function both before and after surgery [4].…”
Section: Introductionmentioning
confidence: 99%
“…The IIEF, which was used in this study, is most commonly used as a validated questionnaire on sexual function after rectal cancer surgery. The response rates of each questionnaire also influence the quality of the study, with complete response rates reported to range from 21% to 100% [3,[8][9][10]14,17,19,28,[30][31][32][33][34]. It can be difficult to get good response rates on questionnaires on sexual function due to embarrassment.…”
Section: Discussionmentioning
confidence: 99%